Investigation of the Luminescence Spectral Profiles and the Efficiencies of Yb3+, Nd3+, Tm3+ Doped Y2O3-SiO2 Nano-phosphors - ERDEM, MURAT (SPRINGER, 2017)
Among various developed UC luminescence materials, rare earth doped yttrium silicates (YSO) exhibit high chemical durability and thermal stability which are suitable for many applications such as lighting, lasers, optical sensors and biological applications. The reduction to nano size of such materials aims to investigate the issue of how the optical properties affected, and thus to further extend the use of these materials in photonic industry. The studies about the effect of nanoscale to the lattice-electron interaction is not yet enough to understand the mechanisms. For this reason, the influence of the various synthesis techniques to the size and the effect of the size of those nano-materials on the optical and thermal properties are basic research areas for various photonic device design and their developments. In most cases, the rare earth ions replace other ions of similar size and same valence state in the host medium. The dopant ions (Tm3+, Nd3+ and Yb3+) replace the Y3+ ions in the host, randomly. Because of the dopant ions have a different ionic radius than the yttrium ions, they distort the lattice around them. As a consequence, the local environment of the different dopants gives different absorption and radiation energies for each single ion in the host. The selection of host material change the luminescent effects on the emission properties such as obtaining different color in emitted light.